Management of Research Data in ETD Systems - Ubogu, Felix; Sayed, Yasien (My University, 2008)
Purpose To establish the research data management practices in institutions which have ETD programmes. These may include the systems in place (software and hardware), and the integration of data and text. Design/methodology/approach Along with a review of the literature the authors carried out a brief survey of existing practices in the management of the raw data on which a thesis/dissertation is based. A questionnaire was sent to the members of the Networked Digital Library of Theses and Dissertations (NDLTD) and a number of other institutions. Findings Sixty percent of the respondents indicated that their institutions have research data management centres/services. Only in one institution is there a relationship between the ETD programme and the data management centre/service. In this instance, ETDs were previously housed on the Academic Computing Services servers. Most of the institutions have no policy on the stewardship of raw data of a thesis/dissertation, and raw data is only stored if provided by the author along with the full text. Other forms of data pose challenges to institutions, and they are investigating options for including other data such as artwork, datasets and recordings, that form part of the submission. Practical implications The paper will be a source of information to institutions considering embarking on the management of research data, especially that research data on which a thesis/dissertation is based. Originality/value The work draws attention to the need to collect research data of long term value. Such data may for example be utilised for the transfer of knowledge and skills by using postgraduate students to train less experienced students, using the archived/stored data without duplicating costly experiments, or for multiple projects based on the same or expanded datasets.
Keywords: data; management; ETD; research; thesis; dissertation